Production performance and physiological responses of jelawat fish (Leptobarbus hoevenii) breeding maintained in different containers - Eko Harianto; Muhammad Sugihartono; Muarofah Ghofur; Safratilofa Safratilofa; Muhammad Yusuf Arifin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Jelawat fish cultivation activities are still experiencing problems with low production. In order to increase the production of jelawat fish seeds during the grow-out phase, research needs to be carried out regarding the type of containers for the cultivation. This research aims to determine the best type of container for jelawat fish (Leptobarbus hoevenii) breeding regarding production performance and physiological responses. This study used a completely randomized design with four different treatments in rearing containers and three replications including aquarium (A), fiber tanks (B), concrete tanks (C) and floating net cages (D). The fish seeds used in this study were 2.76 0.15 cm long and weighed 0.17 0.17 g. During breeding process, the fish were given commercial feed with a protein content of 41% and air changes were carried out at 30% of the total air volume every 2 days. The parameters observed in this research include production performance, physiological responses, and air quality. The research results showed that different types of rearing containers had a significant effect on production performance parameters, total cholesterol, and hemoglobin. Total cholesterol and hemoglobin at the start of cultivation were 191 mg/dL and 11.6 g/dL, decreasing at the end of cultivation to 120.28-141.59 mg/dL and 9.03-12.83 g/dL. Air quality was still within the appropriate range for rearing jelawat fish seeds.Keywords:Aquariumsconcrete tanksfloating net cagestarpaulin pondsjelawat fish